Influence of English and Filipino as Assessment Languages in Word-Problem Performance - Cacho, Reynald; Lladonez, Stephanie Alyssa; Villenes, Rejulios; Macabuhay, Mary Rose; Valerio, Crizia Nicole (OKARA: Jurnal Bahasa dan Sastra, 2024)
Second-language learners frequently encounter challenges when solving word problems that are not written in their first language. This study compares the mathematics word-problem performance of 5th-grade learners using English and Filipino as the languages of assessment. The study consists of 32 5th-grade students from a public elementary school in the Philippines. The lesson delivery focused on problem-solving learning competencies, delivered by an experienced teacher using English-language instruction. Employing a quasi-experimental design, the researchers utilized a researcher-made 30-item test comprising questions expressed in English and 15 questions expressed in Filipino. Each student responds to questions in both languages. It was administered at the beginning and the end of a week-long lesson. Analyses of test scores yielded no significant difference between learners’ performance in English and Filipino items; however, results reveal students’ very low competency in solving word problems. Nonetheless, this study supports the utilization of bilingual instruction and the inclusion of Filipino translations in assessments aside from offering research points for further explorations.